Limites e desafios do cargo de orientação pedagógica na rede municipal de Sorocaba - Almeida, Luana Nogueira de (Universidade Federal de São Carlos, 2024)
The object of this study is the position of pedagogical guidance in the municipality of Sorocaba. The investigation identified the limits and challenges of this position, based on the study of scientific productions on school management. The central question of the research was to understand the responsibilities of the pedagogical guidance position to verify its specificities, considering that it combines functions traditionally performed by educational guidance and pedagogical coordination. To understand the position of pedagogical guidance, we conducted a literature review and did a comparative study of the duties of positions with similar functions in the education departments of Sorocaba and São Paulo - city. In the end, we believe that the duties and actions of pedagogical guidance show an overload of professional functions, not only because it brings together the positions of pedagogical coordination and educational guidance, but also because of the lack of delimitation of the end-activities of this professional, compared to their actions in the daily life of school units in the municipality of Sorocaba.
Limits and challenges of positioning pedagogical guidance in the municipal network of Sorocaba
Keywords: Gestão Escolar; Orientação Pedagógica; Coordenação Pedagógica; Orientação Educacional; School Management; Pedagogical Guidance; Pedagogical Coordination; Educational Guidance; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL